Aspecto lírico-religioso das canções marianas: um estudo sobre as metáforas e metonímias que representam Maria - Cás, Lauro Edson da (My University, 2014)
This study analyzes the religious lyrical aspect of three Marian songs, collected from the book Cancioneiro Popular do Imigrante Italiano na Região de Colonização Italiana, and also intends to clarify, using metaphors and metonymies, the representation of Mary. To do that, this study takes into consideration imprescindible issues such as History, Culture, Identity, Religiosity, and Mariology, Metaphors, Metonymies (Conceptual Metaphor Theory) and music. This dissertation is structured upon four chapters as follows: the first chapter links History and Culture, trying to revise some relevant points of the history of the Italian immigration on the RCI in the Northeast Region of our state, focusing on the importance of religion and/or faith since the beginning of that process. Therefore, there is the analysis about the Region, Identity and Religiosity. The second chapter highlights the Cancioneiro Popular and then, the Popular Oral Tradition. Also, it deepens the aspect of popular culture expressed by the songs and brings into evidence the characterization of the Marian Songs (origins, ritualism and devotion of the Italian immigrant). Moreover, it shows some aspects of the Marian devotion, so present and alive within the immigrant, because Mary is described as the mother who is always with her children (the people). The third chapter, in turn, focus on the analysis of aspects of the Conceptual Metaphor Theory , of the Symbolism, and also of the interpretation and research regarding the Virtues, aiming at analyzing the idealized woman´s portrait , or still, the representation of the mother Mary (Madonna). At last, presented in the fourth chapter are the Methodology and the Analysis of the Marian Songs, that is, the analysis of the corpus of songs: Beléssa di Mary, Mary Consolatrice and O Bela mia Speransa that motivate the study. This part follows the method of semantic analysis, based on George Lakoff (and collaborators) that permeates the study of the conceptual metaphors. There is the ethnographic position as well, where is emphasized the field work carried out to know opinions and perspectives of the people, going beyond the researcher´s analysis. After that, the synthesis is done with the obtained results by the research/study.
Este trabalho analisa o aspecto lírico-religioso de três canções marianas, recolhidas do Cancioneiro Popular do imigrante italiano na Região de Colonização Italiana e se propõe revelar, sob o aspecto das metáforas e das metonímias, a representação de Maria. Para tanto, este estudo dialoga com temas imprescindíveis para a obtenção de resultados, como História, Cultura, Identidade, Regionalidade, Mariologia, Metáforas, Metonímias (a Teoria de Metáforas Conceituais) e música. Assim sendo, a dissertação está estruturada sobre quatro capítulos que norteiam a análise e a interpretação. A saber: o Primeiro Capítulo entrelaça a História e a Cultura, procurando fazer uma revisão de aspectos relevantes da história da imigração italiana na RCI na Região Nordeste do Estado, focando a importância da religião e ou da fé desde os primórdios desse processo. A partir disso, há a análise sobre Região, Identidade e Religiosidade. O Segundo Capítulo destaca o Cancioneiro Popular e assim, o aspecto da Tradição Oral Popular. Aprofunda o aspecto da cultura popular expressada com o canto e traz em evidência a caracterização do Canto Mariano (origens, ritualismo e devoção do imigrante italiano). Demonstra, ainda, aspectos da devoção mariana, tão presente e viva junto ao imigrante, pois Maria é descrita como sendo a mãe que está sempre presente e junto aos seus filhos (povo). O Terceiro Capítulo, por sua vez, concentra a análise dos aspectos da Teoria da Metáfora Conceitual, da Simbologia e, também, da interpretação e pesquisa sobre as Virtudes, objetivando a análise da figura da mulher idealizada , ou ainda, da representação da mãe - Maria (Madonna). Por fim, no Quarto Capítulo, tem-se a Metodologia e a Análise das canções marianas, ou seja, a análise do corpus das canções: Beléssa di Maria; Maria Consolatrice; O Bèla mia Speransa, que motivam este estudo. Esta parte segue o método da análise semântica com base em George Lakoff (e colaboradores) que permeiam o estudo das metáforas conceituais. Há, também, a posição etnográfica, onde é destacada a pesquisa de campo realizada para conhecer opiniões e perspectivas do povo, indo além da análise do pesquisador. Após isso, é feita a síntese com os resultados obtidos pela pesquisa/estudo.
Keywords: Lingüística, Letras e Artes; Cancioneiro popular; Cantos paralitúrgicos; Cultura; Identidade; Imigração italiana; Literatura popular; Memória; Religiosidade popular; Região; Região colonial italiana (RS); Representação; Maria, Virgem, Santa; Simbologia; Metáfora; Metonímia; Música popular cristã; Cancioneiro popular; Paraliturgic chants; Culture; Identity; Italian immigration; Popular literature; Memory; Popular religiosity; Italian colonial region, RS; Representation; Mary, Blessed Virgin; Simbology; Metaphor; Metonomies; Contemporary christian music